Influência da adição de Nb-B na microestrutura de solidificação da liga Al-0,8%Mg-0,7%Si (6201) - Sousa, Sarah Maria de Albuquerque (2022)
The AA6201 alloy, widely used in the manufacturing of power cables, was modified by the addition of a Al-Nb-B master alloy in order to investigate the possible effects on the microstructure. Therefore, the Al-0.8%Mg-0.7%Si (AA6201) and Al-0.8%Mg-0.7%Si-0.5%Nb-0.1%B alloys were directionally solidified. in a transient heat extraction regime and solidified rapidly by means of centrifugal solidification, to ensure a broad spectrum of cooling rates and microstructures, which can be correlated with each other. Analyses were performed on determining both dendritic spacings (λ) and grain size (GS). While the directionally solidified Al-0.8%Mg-0.7%Si (6201) alloy presented exclusively columnar grains, the addition of Nb-B favored the occurrence of a columnar to equiaxial transition CET in the modified casting and, in addition, a reduction in grain size, either for columnar or equiaxial grain morphologies, promoting a reduction of up to 13 times the average value of grain size. Within the range of directional solidification cooling rates (0.5 to 33 °C/s), it was observed that for the ingot with the addition of 0.5%Nb-0.1%B there was high cooling rate-cells arrangement for cooling rates greater than 5.5 °C/s and minimal variation in secondary dendritic spacing. However, the fast solidification conditions revealed that increasing the cooling rate (~240 °C/s) reduced both TG and λ2. It was proposed that the TG/λ2 ratio could characterize the micromorphology of the α-Al cells that grew in the modified 6201 alloy, occurring when the ratio was less than 6. Finally, tensile properties were determined for several samples and related to different λ2 and GS values through the proposition of Hall-Petch types equations, where it was observed that the ultimate tensile strength of the alloy containing Nb-B (~190 MPa) was higher than that observed for the alloy without Nb-B.